Analysis of the profitability of the semi-intensive system of fattening cattle with semi-confinement (Research, Society and Development, 2022)
Beef cattle in the semi-intensive system with semi-confinement has been growing in the state of Rondônia. It is the raising of beef cattle with supplementation of concentrates (rations) in the last phase of the fattening cycle. This system requires greater financial control, due to the high cost of production. Therefore, it is necessary to carry out financial analysis, that is, to assess the costs, revenues, investments, contribution margin, profitability and profitability of the business. This makes it possible to manage the business, since, with financial knowledge, it is possible to make more assertive decisions. The research had as objective to analyze the costs, the contribution margin and the profitability in the properties with bovine fattening with semi-confinement system. The research methodology was descriptive and exploratory, deductive method, with a quantitative approach. Bibliographic and documentary research and field research were carried out with application of a form and non-participant observation. The result of the research found that the average contribution margin was 18.75%, that is, in this activity around 81% of the revenue will cover variable costs, since these are the ones with the greatest degree of difficulty in being reduced. Profitability ratios averaged 13.5% and average monthly profitability was 0.38%. Given the importance of cattle farming in the state of Rondônia and the analyzes carried out, it is suggested that the production of beef cattle should be analyzed with greater emphasis on the question of costs inherent to the activity, depreciation and depletion of pastures, such as the amount of annual slaughter, which can provide better financial results.